(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2024)
This study aims to Utilizing Folktale Movie Increase the student vocabulary. the research used a classroom action research method that adopted the Kemmis and McTaggart designs. the procedure includes planning, implementation, observation, and reflection. the research includes two cycles consisting of four meetings in each cycle. the participants of this study were 30 students of class VII. in collecting data obtained from observation sheets, documentation, and written tests. researchers used pre-test and post- test achievement tests. the results showed that using folktale movie had succeeded in increasing students vocabulary mastery. some students gradually got good grades in the second cycle. based on the observations, students enjoy the whole teaching and learning process because this technique encourages students to be more active and accept challenges they never did before.